Ciência, tecnologia, sociedade e ambiente (CTSA) no ensino de microbiologia para crianças: pesquisa-ação em uma escola municipal de Santa Helena/Paraná - Angonese, Camila (2023)
Microbiology is the science that studies microorganisms and their role in the world, society, the human body, and the environment, contributing to maintaining balance on the planet. Microorganisms, widely used in products and processes by humanity, allow teaching and learning procedures countless connections with students' daily lives. However, the superficial, fragmented and traditionalist approach to microbiological content provides a perception as something abstract, pathogenic and harmful to human health and the environment. According to these statements, the research focused on the importance of a way of teaching that promotes correlations between science, technology, society, and the environment (STSE perspective) for children in Elementary School. The objective was to evaluate the pedagogical contributions of Teaching Sequencing (TS) on microorganisms, developed in the STSE approach, for fifth-grade students of a municipal school in Paraná. The research was qualitative, action research; with activities organized in five pedagogical meetings of four hours class each, with video recording and notes taken by the researcher. The analysis data got from the activities developed by the students during the TS (their communications through drawings, texts, and molding) besides a closing survey. The analyzed data were according to theoretical and methodological assumptions of content analysis. Three Context Units (CU) emerged from the data (Types of microorganisms, The social and environmental importance of microorganisms, and Technologies used in teaching and learning processes of microorganisms) besides Units of Analysis (UA) arising from the activities and the survey. In general, the study showed that the development of TS in the STSE perspective enabled the construction of knowledge related to the benefits of microorganisms to human beings and the environment. In the first UA of the activities, 75% of the students referred to microorganisms as causing diseases, linking them to Coronavírus (COVID-19). In the first UA of the closing survey, only 12.5% of the students referred to the harmful effects of microorganisms, 37.5% started to refer to the benefits to human beings, 45.8% to the benefits to the environment. Comparing both UAs, in the second CU there was a reduction in perceptions of the harm and benefits of microorganisms to humans and an increase in consciousness related to the environment's benefit (from 16.7% to 45.8%). Regarding the last CU, the students showed conversance and interest in the digital technological resources used which may be related to the emergency remote teaching period in which computers, cell phones, and digital platforms began to be incorporated into many teachers' practices. That same conversance was not identified in the UA related to practical classes and usage of the microscope, where students participated with interest and numerous requests for more activities of this type. In general, the study showed the viability of teaching in the STSE approach to promoting Microbiology learning among Elementary School students.